Artificial intelligence and psychoanalysis: is it time for psychoanalyst.AI? - Rabeyron, Thomas (Frontiers in Psychiatry, 2025)
The current development of artificial intelligences (AI) is leading to major transformations within society. In this context, we observe how some of these AIs are spontaneously used by individuals as confidants, and even as romantic partners. The emergence of such relationships with AIs raises questions about their integration in psychiatry and the possibility of developing “digital therapists”. In this regard, we highlight four key elements (accessibility and availability; confidentiality; knowledge; memory) to compare what an AI offers in comparison to a human therapist. We also discuss the results of the studies that have already investigated the use of such AIs in psychotherapy, particularly in the fields of depression and anxiety. We then propose to reflect more specifically on the possibility of creating a “psychoanalyst.AI,” which leads us to examine the elements of the therapeutic relationship (transference, free association, play, dreams, reflexivity, and narrativity) with an AI. In conclusion, we offer some reflections on the relevance of considering AIs as “therapeutic artifact,” while taking into account the ethical issues raised by the use of AIs in therapeutic settings.